(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2009)
Antonio Berini (Rome 1770-Milan 1861), famous gem-engraver, before 1804 decided to move from Rome to Milan, the capital of the Kingdom of Italy, where he lived, estemeed and praised; he was employed by the court and prestigious art patrons to engrave intaglios and cameos.A big collection of 114 plaster casts of intaglios and cameos made by Berini, without explanations, is now in the Civici Musei of Storia and Arte in Trieste, part of the bequest of Filippo Zamboni, cosmopolitan man of letters. These casts are a Berini’s very interesting “instrument of work”: in fact there are multiple casts and casts of works of other gem-engravers. Zamboni knew Berini very well; he writes that the artist was able to imitate ancient intaglios and cameos so perfectly that his engravings were mistakenly thought ancient. The subjects analysed in this article are common and often engraved by the artists of the second half of Eighteenth Century - first half of Nineteenth Century: the famous intaglio known as the Strozzi Medusa (reproduced by almost all engravers), Atena/Minerva/Roma’s head, Esculapio’s bust, Paride’s bust, gems depicting Famous Men, as Mecenate, Dante, Petrarca, Leonardo da Vinci, Michelangelo, Raffaello, Shakespeare, Alessandro Tassoni.